Herpes Simplex Virus type 1 inhibits autophagy in glial cells but requires ATG5 for the success of viral replication - Ripa, Inés; Andreu, Sabina; Josa-Prado, Fernando; Fernández Gómez, Beatriz; de Castro, Fernando; Arribas, María; Bello-Morales, Raquel; López-Guerrero, José Antonio (Frontiers in Microbiology, 2024)
Herpes Simplex Virus type 1 (HSV-1) 1 is a neurotropic virus that has been associated with neurodegenerative disorders. The dysregulation of autophagy by HSV-1 has been proposed as a potential cause of neurodegeneration. While studies have extensively tackled the interaction between autophagy and HSV-1 in neurons, research in glial cells is currently limited. Our studies demonstrate that HSV-1 inhibits, but not completely blocks, the formation of autophagosomes in human oligodendroglioma- and astrocytoma- derived cell lines. These findings have been confirmed in murine oligodendrocyte precursor cells (OPCs). Finally, this study investigates the impact of autophagy on HSV-1 infection in glial cells. While the lack of basal autophagy in LC3B knockout glial cells does not have a significant effect on viral infection, cells without the autophagy-related protein ATG5 exhibit reduced viral production. The absence of ATG5 leads to a decrease in the transcription and replication of viral genes, as well as a delay in the initial stages of the formation of HSV-1 replication compartments. These findings indicate that while autophagy may not play a significant role in antiviral defense in glial cells, HSV-1 may be inhibiting autophagy to exploit non-canonical functions of certain components of the autophagic machinery, such as ATG5, to benefit its lifecycle.